(3eTjNI HgGA GdOjf CHj eMeO GdbGSe Hf eXaQ Hf eMehO Hf YSGcQ GdOeTbis - (3eMeO Hf CMeO Hf eMeO GdHQRGdj GdeZQHj GdeGdcj, CHh GdbGSe,J (B844 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdeMOK CHh ESMGb EHQGgje GdNThYi s
(3BNQgG (B:s
(3Yf YdbeI Yf YHO Gddg bGd (B: (3CYa GdfGS bJdI Cgd GdEjeGf s
(3cJHJ Yf fSNI HChdgG bQGAI deMeO Hf QLGA Hf eMeO GdbjSi Ydi UGMH GdeTjNI GHf YSGcQ SfI (B622s
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: 722s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs